Comparison in trends and outcomes of multiple vs. single arterial coronary bypass graft surgery - Ding, Qiuju; Li, Han; Cheng, Xiaofeng; Ge, Min; Zhou, Qing (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveMultiple arterial grafting (MAG) has been suggested to confer long-term survival benefits for patients undergoing coronary artery bypass grafting (CABG), yet its short-term benefits remain uncertain. This study aims to analyze the impact of MAG on in-hospital outcomes and identify potential risk factors.MethodsA retrospective analysis was conducted from all patients who underwent CABG surgery in our development from January 2022 to December 2024. A generalized mixed-effects model and sensitivity analysis were employed to evaluate the influence of the type of CABG bypass graft on in-hospital major adverse cardiac and cerebrovascular events (MACCEs), postoperative dialysis, intra-aortic balloon pump (IABP) use, re-thoracotomy for bleeding and sternal wound infection (SWI).ResultsA total of 960 patients were included in this study. Patients who received MAG surgeries had more coronary artery lesions observed preoperatively. Compared with patients who underwent single arterial grafting (SAG), those who received MAG surgery did not show significant differences in the incidence of in-hospital MACCEs, postoperative dialysis, IABP use, re-thoracotomy or SWI. Interestingly, good left ventricular function was associated with a reduced occurrence of postoperative dialysis, MACCEs, and IABP application. Chronic renal insufficiency emerged as a risk predictor of major in-hospital adverse events.ConclusionThis single-center study did not find significant differences in short-term outcomes between MAG and SAG groups. However, caution should be exercised when applying these findings to other clinical environments and patient populations. Further multi-center, prospective randomized controlled trials (RCTs) are needed to validate and extend our results.